Imagens sonoras: uma proposta de leitura de A Canção de Lisboa - Barreira, Hugo (2018)
This article aims to propose a new understanding of the film A Canção de Lisboa (1933) by Cottinelli Telmo based on the analysis of the role of music and sound in the film. The study of the film was grounded on a documentary survey and a set of views of a digital copy of agreement and which resulted in some descriptive instruments. Considering that this is the first sound film entirely produced in Portugal, the analysis of the 1933 film will be preceded by a first part, a contextualization, which presents some of the possibilities explored in the transition from mute to sound in a national context.